1996
DOI: 10.1093/ajcn/63.4.546
|View full text |Cite
|
Sign up to set email alerts
|

Gastrojejunal kinetics and the digestion of [15N]beta-lactoglobulin and casein in humans: the influence of the nature and quantity of the protein

Abstract: The evolution and luminal effects of different quantities of casein and beta-lactoglobulin were investigated in the upper jejunum of 35 volunteers who ingested 400 mL water with either beta-lactoglobulin or casein in either low or high doses (72.6 mmol N, Lbetalg; 71.7 mmol N, LCas; 368.2 mmol N, Hbetalg; 386.8 mmol N, HCas). The flow rate of the liquid effluents as well as the nitrogen movements were measured and the exogenous ([15N]) and endogenous nitrogen fractions analyzed in the upper jejunum after milk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
143
0
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(154 citation statements)
references
References 23 publications
8
143
0
3
Order By: Relevance
“…Rate of gastric emptying and gastric distension, delay in nutrient±receptor contact in the small intestine, levels of circulating nutrients, insulin, glucagon and cholecystokinin, and oxidation of macronutrients are known to be related to satiety (Stubbs, 1995;Read et al, 1994;Koopmans et al, 1991;Holt & Miller, 1995;Geary, 1990;Peikin, 1989). Varying the quality of dietary protein may affect some of the intermediate physiological processes: digestion, gastric emptying and the composition of intestinal ef¯uents (Mahe  et al, 1996;Baglieri et al, 1995), rate of amino acid absorption and digestion (Re Ârat, 1993;Collin-Vidal et al, 1994), plasma and brain amino acid concentrations and pattern (Anderson et al, 1994;Uhe et al,1992), and insulin and glucagon releases (Nutall & Gannon, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rate of gastric emptying and gastric distension, delay in nutrient±receptor contact in the small intestine, levels of circulating nutrients, insulin, glucagon and cholecystokinin, and oxidation of macronutrients are known to be related to satiety (Stubbs, 1995;Read et al, 1994;Koopmans et al, 1991;Holt & Miller, 1995;Geary, 1990;Peikin, 1989). Varying the quality of dietary protein may affect some of the intermediate physiological processes: digestion, gastric emptying and the composition of intestinal ef¯uents (Mahe  et al, 1996;Baglieri et al, 1995), rate of amino acid absorption and digestion (Re Ârat, 1993;Collin-Vidal et al, 1994), plasma and brain amino acid concentrations and pattern (Anderson et al, 1994;Uhe et al,1992), and insulin and glucagon releases (Nutall & Gannon, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…These differences in the postprandial metabolic response may be explained by modi®cations in the rate of gastric emptying and by the effect of amino acids on the pancreatic endocrine response. The measurement of gastric emptying could not be performed in this study, but it is well known that casein precipitates in the stomach and, when loaded in suf®cient amount, signi®cantly reduces the rate of gastric emptying (Mahe  et al, 1996;Hara et al, 1992). The present study shows for the ®rst time that, in humans, postprandial Figure 4 Plasma insulin concentrations and insulin AUCs in response to the six protein-and energy-manipulated meals.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 On the basis of their absorption pattern, dietary proteins can be divided in so-called fast and slow digestible proteins. 14 Fast proteins, such as whey protein, are soluble, whereas slow proteins, such as casein, clot in the stomach resulting in a delay in gastric emptying 15,16 and lower but more sustained plasma amino-acid elevations after ingestion compared with fast proteins, 14,16,17 which may be associated with differences in hormonal and thermogenic responses. 18 Hall et al 17 found that higher postprandial circulating levels of amino acids are associated with increased satiety and suggested that fast proteins are, therefore, more satiating than slow proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors [4,5,39] observed a net portal appearance of amino nitrogen and amino acids as soon as 30 min after feeding a diet containing casein as the exclusive protein source. Other authors [18] noted that the exogenous nitrogen appeared during the first 20 min after ingestion of casein.…”
Section: Discussionmentioning
confidence: 94%